2021
DOI: 10.1097/prs.0000000000007828
|View full text |Cite
|
Sign up to set email alerts
|

The Nasoalveolar Molding Cleft Protocol: Long-Term Treatment Outcomes from Birth to Facial Maturity

Abstract: left lip and palate are the most common congenital anomaly of the face. Although the optimal indications and treatment protocols continue to be debated, one of the most actively discussed therapies is nasoalveolar molding. [1][2][3] Supporters of nasoalveolar molding cite statistically significant improvements in nasal symmetry in patients who undergo the treatment compared with those who do not, 4,5 benefit to nasal aesthetics as judged by caregivers and surgeons, 6,7 greater benefit to columellar length in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 72 publications
(118 reference statements)
1
19
0
Order By: Relevance
“…It has been shown to obviate the need for secondary bone graft in as high as 72% of patients, does not significantly limit facial bone development, and has a low incidence of cleft lip and nasal revision. 11,18,25 This study was limited to short term surgical outcomes and demonstrated that addition of GPP to cleft lip repair did not increase post-operative complications or 30-day readmission when compared to cleft lip repair alone.…”
Section: Face 3(3)mentioning
confidence: 87%
See 2 more Smart Citations
“…It has been shown to obviate the need for secondary bone graft in as high as 72% of patients, does not significantly limit facial bone development, and has a low incidence of cleft lip and nasal revision. 11,18,25 This study was limited to short term surgical outcomes and demonstrated that addition of GPP to cleft lip repair did not increase post-operative complications or 30-day readmission when compared to cleft lip repair alone.…”
Section: Face 3(3)mentioning
confidence: 87%
“…It is notable that many of the leading cleft centers performing NAM complete presurgical infant orthopedics within 3 months in a patient with a unilateral cleft and 5 months in a patient with a bilateral cleft. 10,17-19…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Every day there are many ideas and innovations regarding precise job in rhinoplasty, 21 aesthetic surgery 22 and reconstructive surgery. 23,24 That includes nasal reconstruction, 23 cleft lip and palate nasal deformity 25 regarding appearance, 26 function, respiratory problems 27 and skeletal maturation 28 which are still points of research that shows a flow of ideas and innovations.…”
Section: Discussionmentioning
confidence: 99%
“…20 Previous studies of patients with UCLP suggest that NAM does not significantly affect facially mature cephalometric measures for midface growth. 21 However, the effect of NAM on maxillomandibular proportions for patients with BCLP has not been evaluated with cephalometric analysis spanning from birth to facial maturity.…”
mentioning
confidence: 99%